Beginning Neo4j - Kemper, Chris; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2015)
Beginning Neo4j is your introduction in the world of graph databases, and the benefits they can bring to your applications. Neo4j is the most established graph database on the market, and it's always improving to bring more of its benefits to you. This book will take you from the installation of Neo4j through to building a full application with Neo4j at its heart, and everything in between. Using this book, you'll get everything up and running, and then learn how to use Neo4j to build up recommendations, relationships, and calculate the shortest route between two locations. With example data models, best practices, and an application putting everything together, this book will give you everything you need to really get started with Neo4j. Neo4j is being used by social media and ecommerce industry giants. You can take advantage of Neo4j's powerful features and benefits - add Beginning Neo4j to your library today.
1. Chapter One: Introduction to Graph Databases -- 2. Chapter Two: Getting to Know Neo4j -- 3. Chapter Three: Get Up and Running with Neo4j -- 4. Chapter Four: Meet Cypher -- 5. Chapter Five: Managing Your Data in Neo4j -- 6. Chapter Six: Importing and Exporting Data -- 7. Chapter Seven: Using Data in Neo4j -- 8. Chapter Eight: Building an App in Neo4j -- 9. Chapter Nine: Neo4j in Production.
Keywords: Computer programming; Programming languages (Electronic computers).; Application software; Web Development; Programming Languages, Compilers, Interpreters; Computer Appl. in Administrative Data Processing